Hemodynamic relationship between intracranial aneurysm and carotid stenosis - Jou, Liang-Der (2013)
Objective: Coexistence of both an intracranial aneurysm and a stenosis at the same internal carotid artery is infrequent, but it may complicate therapeutic management of either disease. It is unclear if a stenosis plays any role in development of intracranial aneurysms. We study patients with intracranial aneurysms at our hospital and investigate if there is a relationship between a carotid stenosis and an intracranial aneurysm. Methods: Two hundred and nine patients who were treated for their intracranial aneurysms in a 2-year period were reviewed. Fifty-four patients were found to have at least one intracranial aneurysm and one intracranial or extracranial carotid stenosis. Ten of them had bilateral stenoses; 17 aneurysms were on the ipsilateral side of the stenosis, and eight on the contralateral side. Nineteen aneurysms were elsewhere. Two cases were selected for detailed computational fluid dynamics (CFD) analyses: one with an intracranial and the other with an extracranial stenosis. Results: Aneurysms on the contralateral side of a carotid stenosis are significantly larger than those aneurysms on the ipsilateral side or with bilateral stenoses (13.6 versus 6.6 mm; P < 0.01). CFD studies show that wall shear stress at the aneurysm is more likely affected by an adjacent intracranial stenosis than by an extracranial stenosis. Conclusions: Intracranial carotid aneurysms contralateral to a carotid stenosis are significantly larger than aneurysms with a carotid stenosis elsewhere. Rupture can occur on aneurysms with an extracranial carotid stenosis on the contralateral side or with an intracranial carotid stenosis on the ipsilateral side.